Gastric Neuroendocrine Tumors: Case Series - Dal Pizzol, Alexandre César (2010)
Introduction: Gastric neuroendocrine tumors of the stomach, also known as gastric carcinoids, are derived from enterochromaffin cells of the stomach. Despite being a rare neoplasm, they deserve special attention due to their distinct and less aggressive behavior compared to gastric adenocarcinoma. Objective: To analyze in retrospect the cases of gastric neuroendocrine tumors treated at the Abdominal-pelvic Surgery Service of the Brazilian National Cancer Institute; to devise the pre-operation and treatment routines for the gastric carcinoid. Material and Methods: We performed a retrospective analysis of the experience of the Brazilian National Cancer Institute concerning the management of these tumors from 1997 to 2008. Results: Seventeen cases of gastric carcinoid tumors have been reported. After an extensive review of the subject, the new staging as well as the treatment for gastric carcinoid tumor were applied according to the guidelines provided by European Neuroendocrine Tumor Society and to our study. Conclusion: Gastric carcinoid tumors require an individualized treatment in order to avoid unnecessary or very conservative aggressive therapies. The staging and treatment guidelines proposed by the European Neuroendocrine Tumor Society proved reproducible and easy to apply regarding the prognosis, and are currently established as routines of this Service.